Cu Metal/Mn Phthalocyanine Organic Spinterfaces atop Co with High Spin Polarization at Room Temperature. (21st May 2018) - Urbain, E.; Ibrahim, F.; Studniarek, M.; Nyakam, F. Ngassam; Joly, L.; Arabski, J.; Scheurer, F.; Bertran, F.; Le Fèvre, P.; Garreau, G.; Denys, E.; Wetzel, P.; et al.
Abstract: The organic spinterface describes the spin‐polarized properties that develop, due to charge transfer, at the interface between a ferromagnetic metal (FM) and the molecules of an organic semiconductor. However, assembling this interface may degrade the properties of its constituents. To circumvent this issue, one can separate the molecular and FM films using a less reactive nonmagnetic metal (NM). Spin‐resolved photoemission spectroscopy measurements on the prototypical system Co(001)//Cu/Mn‐phthalocyanine (MnPc) reveal at room temperature a high spin polarization P of the Cu/MnPc spinterface atop ferromagnetic Co. Surprisingly, it is found that the Cu thickness dependence of P remains essentially constant up to 10 monolayers (ML), which is inconsistent with the description of indirect exchange coupling between the Co layer and the molecule's Mn site. Ab initio calculations account for this fundamental discrepancy by showing that the topmost Cu layer before MnPc adsorption is already significantly spin‐polarized, and contributes to the formation of the Cu/MnPc spinterface atop Co. The results open a route toward 1) integrating electronically fragile molecules within organic spinterfaces and 2) electrically manipulating molecular spin chains using the well‐documented spin‐transfer torque properties of the FM/NM bilayer. Abstract : Spin‐resolved photoemission spectroscopy measurements on the system Co(001)//Cu/Mn‐phthalocyanine (MnPc) reveal at room temperature a high spin polarization of the Cu/MnPc interface atop ferromagnetic Co. The Cu thickness dependence of the spin polarization remains essentially constant up to ten monolayers. This is corroborated by calculations, which show that the topmost Cu layer before MnPc adsorption is already significantly spin‐polarized.